Pengaruh Struktur Modal Dan Pengelolaan Aset Terhadap Kemampulabaan Dan Dampaknya Terhadap Nilai Perusahaan Agribisnis Yang Terdaftar Di BEI - Anasthasia Triwulan Budisaptorini (Fakultas Pertanian, 2023)
Agribusiness business has promising prospects, because consumer demand for agribusiness products will never stop, even though it fluctuates. Capital is one of the factors needed by a company, so efforts are needed to attract investors and manage assets as well as possible to increase profits. Investment decisions are determined by investors by considering the profitability and size of the company's assets as collateral for debt. Several previous studies were conducted by Salim and Yadav (2011); Mayangsari (2014); Sunarto and Budi (2009); Azhar and Norizza (2012); Samarakoon et al (2014); Niresh and Velnampy (2014); John and Muthusamy, Gabriel (2013); Tseng and Cheng (2011); Bei (2012) with stock exchange objects in several different countries. Different objects motivated the authors to conduct research on agribusiness companies listed on the IDX with the aim of analyzing the effects of capital structure and asset management on company profitability, analyzing the impact of capital structure and asset management on firm value, analyzing the effect of company profitability and analyzing the effects from capital structure and asset management to corporate value through profitability. This research is a descriptive causality study on agribusiness companies listed on the Indonesian Stock Exchange (IDX). Company data were analyzed by SEM and it was concluded that (1) Capital Structure and Asset Management did not significantly influence Profitability (2) Capital Structure and Asset Management had a significant effect on Firm Value (3) Profitability did not significantly influence Firm Value and (4) ) Capital Structure and Asset Management have no significant effect on Company Value through Profitability. Opportunities that exist in the company for investment in the future need to be considered by comparison relative to projections of internal funding sources for policy making regarding the application of capital structure and asset management to company value with profitability as a moderator, to maximize capital structure and asset management as a The main purpose.